Sensor Resource Sharing Approaches in Sensor-Cloud Infrastructure - Yujin Lim; Jaesung Park (International Journal of Distributed Sensor Networks)
Generally, wireless sensor networks have been designed to support predefined application services. The tight coupling between a network and application limits the usability of sensor data. To increase the utilities of wireless sensor networks, sensor-cloud infrastructure has been proposed to provide an open and flexible platform to gather, store, use, and share data from heterogeneous sensors. In this paper, we introduce sensor-cloud infrastructure and present not only comprehensive technical issues like sensor description and publish/subscribe middleware but also applications using sensor-cloud infrastructure. When the issues are tackled in the development of sensor-cloud system, the attractiveness of new applications and services will considerably be increased for end users.